Mediatization of the Ecological Security in the English Media: Corpus-Assisted Approach - L. A. Kochetova; M. N. Orlaynskaya (Дискурс, 2024)
Introduction. The relevance of the work is due to the interest of linguistics in the issues of  discursive mediatization of socially significant phenomena in the English-language media, in  particular environmental safety as the most important value of modern society. The scientific  novelty of the study lies in establishing the content of the value “environmental safety” on  the basis of systematization and quantification of semantic fields that are correlated with the  main topics that determine the interpretation of this socially significant phenomenon in the  British media and form a discourse-based thesaurus of its representation. Methodology and sources. The paper used corpus linguistics methods and the  interpretative method of discourse analysis. The empirical basis of the study was a corpus  of media texts of high-quality and popular media devoted to environmental safety issues,  the corpus size was more than 200 thousand words. Results and discussion. Based on corpus analysis, semantic fields were identified that  represent the concept under study in the high-quality and popular British press. It is shown  that in the media narratives of the British media, ES is closely associated with climate change  and global warming. It was revealed that the dominant topics in narratives about  environmental security in both types of media are: 1) the environment; 2) science; 3) politics.  A comparative analysis of the semantic fields showed the predominance of the semantic  field “science” in high-quality media, which indicates rational and logical strategies for  influencing a wide readership. In the texts of popular media, the semantic field “politics”  dominates, which indicates the politicization of the discourse of environmental safety and  indicates a strategy of emotional impact on the addressee. Both corpora emphasize the  issues of climate change, related to unfavourable weather conditions and extremely high  temperatures, however, high-quality press texts mention temperature anomalies much  more often, which indicates an attempt to arouse public concern about the existing threat  and encourage the adoption of necessary measures. Conclusion. The proposed methodology can be used in analyzing the specifics of other  media discursive practices in terms of their discursive-textual organization, in studying the  rhetorical, pragmatic and linguocultural organization of environmental safety discourse in  sociocultural and ideological perspectives.